2015
DOI: 10.1155/2015/362781
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Anatomy of the Growing Lungs in the Human Fetus

Abstract: Using anatomical, digital, and statistical methods we examined the three-dimensional growth of the lungs in 67 human fetuses aged 16–25 weeks. The lung dimensions revealed no sex differences. The transverse and sagittal diameters and the base circumference were greater in the right lungs while the lengths of anterior and posterior margins and the lung height were greater in the left lungs. The best-fit curves for all the lung parameters were natural logarithmic models. The transverse-to-sagittal diameter ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Contrary to earlier observation of similar right and left lung length, 24 we found significantly shorter right lung length compared to the left. This finding agrees with results from postmortem fetal lung measurements, 25 and seems reasonable as the left side of the diaphragm is placed lower than the right. Our LV measures corresponded to those of Moeglin et al, whose 2D‐based method we adapted 20 .…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to earlier observation of similar right and left lung length, 24 we found significantly shorter right lung length compared to the left. This finding agrees with results from postmortem fetal lung measurements, 25 and seems reasonable as the left side of the diaphragm is placed lower than the right. Our LV measures corresponded to those of Moeglin et al, whose 2D‐based method we adapted 20 .…”
Section: Discussionsupporting
confidence: 91%
“…Concerning the diameters of the thorax, as in the mongoose, the wood pigeon (Columba palumbus) has a greater sagittal diameter in the right lung whereas a greater transverse diameter in the left lung (Alumeri et al, 2013). In the human fetus (Szpinda et al, 2015), similar to the findings obtained for the mongoose, the transverse and sagittal diameters as well as the height were found to be greater in the right lung than in the left.…”
Section: Resultssupporting
confidence: 81%
“…Amabile et al (2016) assessed the 3D reconstruction model of the human thorax and found the thorax and lung volumes to be greater in males than in females. However, there was no significant difference observed in human fetal lung volumes due to genders (Szpinda et al, 2015).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation